Generation Z vs. Generation Y: different from or similar? A comparison of centennials and millennials regarding the use of social media for travel purposes - Andreea Fortuna Șchiopu; Ana-Maria Nica; Ana Mihaela Pădurean; Mădălina-Lavinia Ţală (Cactus, 2023)
The tourists’ decision-making process and sharing behaviors while travelling and social media are intertwined, especially for the young tech-savvy generations. Nevertheless, papers comparing generation Y and Z in this respect are scarce. By surveying two samples, this paper aims to investigate if generations Y and Z are different in terms of social media use for travelling purposes. The results indicate Centennials get more information about journeys from social networks. Moreover, they give more value to online photos during the travel decision-making than generation Y. During the actual journey, Centennials depend less on Facebook and more on Instagram than Millennials. The two samples are significantly different in terms of sharing behavior of their travel experiences. Last but not least, the number of hours spent daily on social media influences the usage of social media while travelling for both generations.